Gaussian process regression analysis for functional data - Shi, Jian Qing.; Choi, Taeryon (Boca Raton, FL : CRC Press, 2011)
The book presents nonparametric statistical methods for functional regression analysis, specifically the methods based on a Gaussian process prior in a functional space.
Includes bibliographical references and index.
rua 30/043/13
Loans
Keywords: Regression analysis; Functional analysis; Gaussian processes